2009
DOI: 10.4161/cbt.8.6.7694
|View full text |Cite
|
Sign up to set email alerts
|

Pheophorbide a based photodynamic therapy induces apoptosis via mitochondrial-mediated pathway in human uterine carcinosarcoma

Abstract: Uterine carcinosarcoma is an aggressive neoplasm with low survival rates because of the lack of very effective chemotherapy protocol. Photodynamic therapy (PDT) is recently suggested to be an efficient protocol for this cancer. Pheophorbide a (Pa) is a chlorophyll degradation product in the green plant cells, its antitumor effect was reported on a number of human cancer cells with PDT approach. This study demonstrated that using Pa in PDT (Pa-PDT) significantly inhibited the human uterine sarcoma cell line MES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
0
40
1
1
Order By: Relevance
“…Pba was shown to cause mitochondria-dependent apoptosis in cultured cancer cells (Tang et al, 2009). In vivo animal models also demonstrated that Pba impedes tumor growth in colon carcinoma and hepatoma xenograft models (Hajri et al, 2002;Li et al, 2007).…”
Section: Orgmentioning
confidence: 97%
See 1 more Smart Citation
“…Pba was shown to cause mitochondria-dependent apoptosis in cultured cancer cells (Tang et al, 2009). In vivo animal models also demonstrated that Pba impedes tumor growth in colon carcinoma and hepatoma xenograft models (Hajri et al, 2002;Li et al, 2007).…”
Section: Orgmentioning
confidence: 97%
“…Pba mediates mitochondrial membrane perturbation and consequent cytochrome c release, resulting in apoptotic cell death (Tang et al, 2009). In addition, PDT destroys tumor microvasculature and causes oxygen depletion within tumors (Dougherty et al, 1998).…”
Section: Role Of C-met/bcrp Signaling In Cancer Resistancementioning
confidence: 99%
“…The levels of ROS and singlet oxygen were immediately increased after Pa-PDT treatment. Singlet oxygen released from Pa-PDT mediated mitochondrial damage (15). We also determined the mitochondrial membrane potential variations (ΔΨm) with use of the fluorescence probe JC-1, the most widely implemented application for detecting mitochondrial depolarization (25).…”
Section: Discussionmentioning
confidence: 99%
“…The energy production with the use of Pa is smaller than that with other photosensitizers, which have to be excited at shorter wavelengths, therefore causing less harm to the surrounding normal tissues (19). Recent studies reported that Pa-based PDT can effectively inhibit tumor cell proliferation in several cancer cells including hepatocellular carcinoma, colon cancer, pigmented melanoma and breast adenocarcinoma (15,18,19). However, Pa-PDT treatment in OSCC has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation